The difference in Nutrition Intake Adequacy AmongInstitutionalized Elderly Residents with and without Sarcopeniaat Nursing Homes in Bandung, West Java - Tirtadjaja, Delia Anastasia; Apandi, Muhamad; Dwipa, Lazuardhi (UI Scholars Hub, 2021)
Introduction. The changes in the elderly’s daily routine including dietary intake and nutritional pattern may cause them to be more susceptible to malnutrition. The changes also increase the risk of sarcopenia that may lead to poor health outcomes such as fall injury, fracture, hospitalization, disability, or even death. Sarcopenia is more likely to occur in a nursing home compared to community settings. This study aimed to determine the difference in nutrition intake adequacy between institutionalized elderly subjects with and without sarcopenia in Bandung, West Java. Methods. A cross-sectional study was held in Ciparay and Budi Istri Nursing Home, Bandung, West Java, Indonesia. Sarcopenia was determined based on the Asian Working Group of Sarcopenia (AWGS) criteria. Nutritional intake was assessed with two non-consecutive 24-hour food recalls and nutritional adequacy was defined based on the American Geriatric Society (AGS) recommendation, which included a total energy intake of ≥ 25kcal/kg BW/day and protein intake of ≥1g/kg BW/day. Results. The present study included 65 older adults, who were categorized into 2 groups, i.e. sarcopenic (31 subjects) and non-sarcopenic groups (34 subjects). Despite the food served having already met daily dietary reference intakes, the sarcopenic elderly subjects showed inadequate nutritional intake (p=0.001) compared to non-sarcopenic elderly subjects. Conclusion. There are differences in nutrition intake adequacy between sarcopenic and non-sarcopenic institutionalized elderly subjects in Bandung. Elderly subjects with sarcopenia had more inadequate nutrition intake than non-sarcopenic elderly subjects.